Optimisme dan Resiliensi Mahasiswa Tahun Pertama di Masa Pandemi COVID-19 - Salsabila, Nada; Jannah, Putri Miftahul; Masyhuri, Masyhuri (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
First-year university students experience transition periods from high school to college level. Despite academic needs, first-year students in the COVID-19 pandemic also face new challenges, such as different peer networks, financial changes, and adaptation. Since resilience is defined as the ability to adapt successfully to pressure and challenges, it is essential to determine what psychological factors contribute to enhancing it. One of the factors related to life adaptation is optimism. Hence, this study aims to observe the relationship between optimism and resilience among university students. The sample comprised 420 first-year students from the UIN Suska Riau (Pekanbaru). Participants completed the CD-RISC Scale and Life Orientation Test (LOT-R). This study performed a linear regression analysis and captured that optimism explained 14.6% of resilience (R²= .146, β=48.163). Thus, identifying the factor influencing students’ adjustment to college life can develop an intervention to help students face this life transition.